Standards Collection Development and Management in an Academic Library: A Case Study at The University of Western Ontario Libraries. - Linda K. Dunn; Shiyi Xie (Issues in Science and Technology Librarianship)
How can academic libraries ensure their standards collections meet the teaching and research needs of science and engineering faculties? Nowadays, most academic libraries face financial constraints that greatly impact collection development. This article documents an academic library's experience with standards collections and the investigation and implementation of an on-demand purchasing model for a high-cost standards collection. [ABSTRACT FROM AUTHOR]